The Role of Electronic Word of Mouth and Social Media Marketing on Brand Image and Purchase Intention toward E-Commerce Cosmetic Products - Hidayat, anas (Archives of Business Research, 2021)
This research aimed to examine the effect of EWOM and Social Media Marketing variables on Purchase Intention with an intervening variable of brand image. This research sampling was carried out using purposive sampling technique from 250 respondents which had the criteria of Indonesian citizens who were interested in buying and using cosmetics through e-commerce and already had income. This research used an analytical tool which is a simultaneous equation model called structural equation modeling. The results of this research indicated that EWOM had a positive and significant effect on brand image and buying intention. Social Media Marketing had also a positive significant effect on brand image,however, it was an insignificant effect on buying intention. Finally, Brand Image showed a positive significant effect on Purchase Intention.